Health Risk Assessment and Determination of Some Heavy Metals in Commonly Consumed Traditional Herbal Preparations in Northeast Ethiopia - Mihreteab Meseret; Gebremariam Ketema; Haile Kassahun (Journal of Chemistry)
Background. Most traditional medicines were prepared from plant origins. These plants could be contaminated by heavy metals, pesticides, and/or toxins. Therefore, the aim of the present study was to determine the level of heavy metals such as lead (Pb), cadmium (Cd), chromium (Cr), and copper (Cu) in frequently used traditional herbal preparations sold in Northeast Ethiopia and to estimate their health risks associated with their daily intake. Methods. A total of 6 traditional herbal preparations were randomly collected from local herbal shops of Dessie and Kombolcha town, Northeast Ethiopia. The samples were prepared for analysis by wet digestion method using nitric acid and hydrochloric acid treatment. The accuracy of the method was analyzed by the spike recovery test. Determination of Pb, Cd, Cr, and Cu by microwave plasma atomic emission spectroscopy was made in herbal preparations traditionally used in Dessie and Kombolcha town, Northeast Ethiopia. By calculating estimated daily intake (EDI), hazard quotients (HQ), and Hazard Index (HI) of metals, the health risk associated with the consumption of the analyzed herbal preparations was also evaluated. Results. The levels of heavy metals were in the range of 3.0–3.92 mg/kg for Pb, 5.35–10.7 mg/kg for Cr, and 0.815–12.3 mg/kg for Cu. However, cadmium was not detected in any of the traditional herbal preparations. This study revealed that the level of Pb and Cu in all analyzed samples was within the WHO maximum permissible limit of 10 mg/kg and 40 mg/kg, respectively. The level of Cr in all traditional herbal preparations was beyond the WHO maximum permissible limit (2 mg/kg). From the health point of view, the HQ value of Cr for KD-03 and KD-04 is greater than 1, suggesting potential health risk. Furthermore, the HI value had revealed that the consumption of KD-02, KD-03, and KD-04 samples had the potential of posing health risks to consumers over long-term consumption of herbal preparations. Conclusion. This study showed that most of the metal concentration levels in the herbal products were within the WHO maximum permissible limits. However, all samples had Cr levels above the WHO maximum permissible limit. Based on the results of this study, there would be a noncarcinogenic health risk to the consumer associated with the consumption of some herbal preparations marketed in Northeast Ethiopia.